Pediatric hospital visits for unintentional drowning in bathtubs in Central Texas, USA - Molly B. Johnson; Barbara D. Cosart; Stewart R. Williams; Brent M. Troy; Karla A. Lawson (Injury Epidemiology)
Abstract Background In the USA, drowning is a leading cause of death for children and the leading cause of death for children 1–4 years old. Bathtubs pose the highest risk of drowning for infants. The aim of this study is to determine factors that increase the risk of drowning in a bathtub for children. Methods This retrospective, cross-sectional study used data retrieved from a hospital-based registry of drowning patients that includes information manually abstracted from patient medical records. This study describes patient characteristics and incident scenarios for children aged 0–17 years who sought care at one children’s hospital for unintentional drowning in a bathtub over a ten-year period, 2014- 2023. Chi-square analysis was used to assess associations between whether a supervising caregiver was present during the incident and the likelihood of hospital admission or the likelihood of poor outcome. Results There were 50 patients 0–9 years old treated for unintentional drowning in a bathtub over the 10-year period. The majority of patients were female (62%), White (86%), or not Hispanic (53%). Most of the patients (84%) were under 2 years old and the majority (56%) were under 1 year old. For most of the patients 2–9 years old, the drowning incident was likely seizure-related. In 91% of the incidents, a caregiver was intending to supervise the child in or around the bath, yet in only 24% of the incidents was the caregiver engaged in supervising the child. The most common reasons for the lapse in supervision was that the caregiver was retrieving a towel and/or clothes (39%) or caring for other children (20%). Chi-square analysis showed that children who were admitted to the hospital for further care were more likely to have no adult caregiver present than those who were discharged after being treated in the Emergency Department only. Conclusions Findings indicate that lapses in supervision are a common cause of bathtub drowning for young children and are associated with the need for higher levels of care. Additionally, results highlight the need for drowning prevention messaging emphasizing gathering all bath supplies before starting a bath and avoiding distractions, such as caring for other children.